Exploring Child and Youth Development: A Case Study of Development Projects Funded by Independent Power Producers (IPPs) in Sutherland, Northern Cape - Rickerts, Caitlin (Stellenbosch : Stellenbosch University, 2026)
Thesis (MA)--Stellenbosch University, 2026.